Marx(ismos) y las teorías de la justicia - Sevilla, Carlos (Foro Interno, 2006)
This article examines certain marxist critiques of the theories of justice that arose after the publication of A Theory of Justice, by John Rawls, in 1971. This book led the field of liberal political theory towards an explicitly normative focus that tended to develop into general theories or in systematic analyses of more specific concepts. In this article we shall broaden the sociological and historical critique of theories of justice based on the debate that began in the pages of the New Left Review.